Extração das lipoproteínas de baixa densidade da gema de ovo de "gallus domesticus" e sua aplicação na criopreservação do sêmen canino - Mariana Machado Neves (2008)
Among the components of the egg yolk, the low-density lipoproteins (LDL) are considered to have the best cryoprotectant effect when freezing sperm cells. The objective of the present study was to evaluate if LDL can substitute the hens egg yolk on cryopreservation of canine spermatozoa. The study was divided in four experiments. The Experiment I was designed to test different concentrations of ammonium sulfate to extract LDL from hens egg yolk, according to the technique of Moussa et al. (2002). The purposes of Experiment II were to elect extenders for centrifugation and freezing which adjusted best to a particular computerized cooling rate. Additionally several thawing temperatures were tested. The substitution of hens egg yolk by different concentrations of LDL, in natural and lyophilized forms, was the aim of Experiment III. The last experiment was designed to test which association - glycerol, dimetilformamide or ethylene glycol with LDL would show better cryoprotectant effect on sperm cells. The conclusions were: 50% of ammonium sulfate concentration extracted best LDL; the substitution of hens egg yolk in Tris-citric extender, by either 9.64, 19.28 or 24.1 mg of LDL in natural form showed to be effective to cryopreserve canine sperm cells; and the association of LDL with glycerol or ethylene glycol showed best results